If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27p + 17q + p + -7q + -5p = 0 Reorder the terms: 27p + p + -5p + 17q + -7q = 0 Combine like terms: 27p + p = 28p 28p + -5p + 17q + -7q = 0 Combine like terms: 28p + -5p = 23p 23p + 17q + -7q = 0 Combine like terms: 17q + -7q = 10q 23p + 10q = 0 Solving 23p + 10q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10q' to each side of the equation. 23p + 10q + -10q = 0 + -10q Combine like terms: 10q + -10q = 0 23p + 0 = 0 + -10q 23p = 0 + -10q Remove the zero: 23p = -10q Divide each side by '23'. p = -0.4347826087q Simplifying p = -0.4347826087q
| 48x=6x | | (55)*7= | | (55)7= | | 7m+3n-2m+9n= | | (5/2)7= | | 3x+5-(2)3=20 | | x^2=0.25 | | 70(x-4)=50x | | x^2-29x-168=0 | | 20x-4=100 | | y(2y-5)= | | 39x=128 | | 42-2x=7x+23 | | f*(2-f)=0.00335570469798658 | | 24r+r(2+r)= | | 3x^2-11x+15=0 | | f*(2-f)=1 | | 0.3*x^3+0.2*x^2+0.5*x=0 | | f*(2-f)=0 | | 0.3*x^3+0.2*x^2-0.5*x=0 | | 3x^2-11x=15 | | -15ab+21ab= | | N-6+7h=42 | | 3x^2-x-1=0 | | 8x-14=66 | | 2c+2=6 | | x^3-x^2+x-1=x^2+1 | | .25(4f-3)=0.05(10f-9) | | 2x^2-11x+25=0 | | 6x^2+19xy+10y^2= | | x^2=0.75x | | 3v^3+7v^2-15v-35= |